Feminization of migration: Redistribution of village government powers and resources to protect women migrant workers - Prastiwi, Juwita Hayyuning (Universitas Merdeka Malang, 2023)
Law Number 18 of 2017 has significantly expanded the role of village governments in protecting migrant workers, specifically by focusing on the social and economic empowerment of Indonesian migrant workers. Within TulungagungDistrict, two villages, Sukorejo Wetan and Tanen have already established. Task Forces for the Prevention and Handling of Violence Against Women Migrant Workers and Laws on the Elimination of Human Trafficking. This research, conducted in these villages, aims to achieve three objectives. Firstly, it seeks to identify the actors involved in protecting women migrant workers and understand the relationships between them. Secondly, it aims to describe the accessibility and role of migrant and post-migrant women’s groups in protecting women migrant workers. Finally, it aims to explore the existence of pro-feminist policies in this context. Using a feminist research methodology, the study employs qualitative methods such as in-depth interviews and document studies. The findings highlight an asymmetric collaboration between civil society groups and the village government, with civil society dominating the formation and implementation of activities by the Officer Unit (Satgas). This a symmetry is intertwined with the absence of resource redistribution from the village government, particularly in terms of budget allocation